All for us and us for all: Introducing the 5R Shared Leadership Program. (November 2020) - Fransen, Katrien; Haslam, S. Alexander; Steffens, Niklas K.; Peters, Kim; Mallett, Clifford J.; Mertens, Niels; Boen, Filip
Abstract: While most leadership programs seek to develop the leadership qualities of the formal team leader, programs that aim to develop the leadership qualities of team members are rare. This article draws on insights from organisational and sport psychology to develop and introduce a new leadership development program — the 5R Shared Leadership Program (5R S ) — that (1) implements a structure of shared leadership (through Shared Leadership Mapping ) and (2) further develops participants' leadership potential (through the 5R's of Readying, Reflecting, Representing, Realising, and Reporting ). More specifically, being a close intertwinement of shared leadership theorising and the social identity approach to leadership, 5R S helps leaders in the team to create, embody, advance, and embed a collective sense of 'us' in their teams. In this article, we aim to shed light on the underpinning theoretical foundation of 5R S, while also sharing insights about how 5R S can be delivered in practice. Furthermore, to provide initial insight into the applicability of 5R S in both organisational and sport contexts, we conducted a longitudinal qualitative comparison study. This involved collecting qualitative data from two initial implementations: with an organisational team ( N  = 16) and a sport team ( N  = 16). A critical reflection on these initial implementations of 5R S leads to recommendations for future efforts to develop shared leadership in organisational and sporting teams. In particular, we highlight the importance of explaining the nature of shared leadership at the start of the program and of having multiple follow-up sessions for participants. In conclusion, by helping leaders in the team to develop and mobilise a sense of 'us-ness', 5R S gives leaders and their teams the tools to create the best possible version of 'us'. Highlights: The 5R Shared Leadership Program ( 5R S ) cultivates the team's leadership potential. The first key aim of 5R S is to implement a structure of shared leadership. Secondly, 5R S draws on social identity principles to develop identity leadership. Qualitative data from an organisation and a sport team evidence the benefits of 5R S . We identify key aspects of 5R S that might be improved in future implementations.